Answer:
z = 3.3
Step-by-step explanation:
Given
2.2 = z - 1.1 ( add 1.1 to both sides )
3.3 = z
The elimination method is ideal for solving this system of equations. By which number must you multiply the second equation to eliminate the
yavariable, and what is the solution for this system?
x + 3y - 42
2x-y-14
OA. Multiply the second equation by-3. The solution is x = 12. y - 9.
ов.
Multiply the second equation by-2. The solution is x-12. y = 10.
OC.
Multiply the second equation by 2. The solution is x - 15, y = 9.
OD
Multiply the second equation by 3. The solution is x - 12. = 10.
Reset
Next
Answer:
D. Multiply the second equation by 3. The solution is x = 12, y = 10
Step-by-step explanation:
Given:
x + 3y = 42 (first equation)
2x - y = 14 (second equation)
To solve by elimination, starting with elimination of the y-variable, multiply the second equation by 3 to get a third equation.
2x - y = 14 (2nd eqn.) × 3
6x - 3y = 42 (3rd equation)
Add the 3rd equation and the 1st equation together.
x + 3y = 42 (first equation)
6x - 3y = 42 (3rd equation)
7x = 84
7x/7 = 84/7
x = 12
To find y, substitute x = 12 in the first equation
x + 3y = 42 (first equation)
12 + 3y = 42
12 + 3y - 12 = 42 - 12
3y = 30
3y/3 = 30/3
y = 10
Solution is x = 12, y = 10
B) 11 square root of 3 end root minus 7 square root of 6
C) negative 3 square root of 9
D) 4 square root of 9
The simplest form of the expression ''7 square root of 3 end root minus 4 square root of 6 end root plus the square root of 48 end root minus the square root of 54'' would be, ''11 square root of 3 end root minus 7 square root of 6''. Hence, option B is true.
Used the concept of the square root of a number that states that,
The square root of a number is the number that, when multiplied by itself, gives the original number.
Given that the expression is,
7 square root of 3 end root minus 4 square root of 6 end root plus the square root of 48 end root minus the square root of 54.
Now, the mathematical form of the expression is,
Simplify each term,
Combine like terms,
It can be written as,
11 square root of 3 end root minus 7 square root of 6.
Hence, option B is true.
To learn more about square root visit:
#SPJ6
Answer:
n = -1 n = -7
Step-by-step explanation:
5| 2n+8| +3 = 33
Subtract 3 from each side
5| 2n+8| +3-3 = 33-3
5| 2n+8| = 30
Divide by 5
5/5| 2n+8| = 30/5
| 2n+8| = 6
An absolute value equation has two solutions, one positive and one negative
2n+8 = 6 2n+8 = -6
Subtract 8 from each side
2n+8-8=6-8 2n+8-8 = -6-8
2n = -2 2n = -14
Divide by 2
2n/2 = -2/2 2n/2 = -14/2
n = -1 n = -7
Symmetric Property
Reflexive Property
Subtraction Property
Answer:
subtraction property
Step-by-step explanation: